Mobile Road Traffic Management System Using Weighted Sensor - Akinboro, Solomon Adegbenro; Adeyiga, Johnson A; Omotosho, Adebayo; Akinwumi, Akinwale O (International Journal of Interactive Mobile Technologies (iJIM), 2017)
Vehicular traffic is continuously increasing around the world, especially in urban areas, and the resulting congestion has become a major concern to automobile users. The popular static electric traffic light controlling system can no longer sufficiently manage the traffic volume in large cities where real time traffic control is paramount to deciding best route. The proposed mobile traffic management system provides users with traffic information on congested roads using weighted sensors. A prototype of the system was implemented using Java SE Development Kit 8 and Google map. The model was simulated and the performance was assessed using response time, delay and throughput. Results showed that, mobile devices are capable of assisting road users’ in faster decision making by providing real-time traffic information and recommending alternative routes.